1999
DOI: 10.1007/s000490050047
|View full text |Cite
|
Sign up to set email alerts
|

The influence of odour on the oviposition behaviour of the cabbage root fly

Abstract: Host plant odours are known to be important in long-range host location by the cabbage root fly, whereas at short distances orientation is mainly visual. We show that olfaction also plays a significant role after a fly lands on a plant and before it moves down onto the soil to oviposit. Host plant acceptance by the cabbage root fly seems to result from a synergistic response to simultaneously perceived olfactory and contact chemostimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Gravid females of the cabbage root fly arrive at a hostplant odour source by a series of short upwind flights, landing and reorientating into the wind between flights (Hopkins et al, 1999). The adult female oviposits in the soil close to the stem of Brassica plants (Nottingham and Coaker, 1985;De Jong and Städler, 1999), while damage to the plants is caused by hatched larvae feeding on the roots.…”
Section: The Cabbage Root Fly (Delia Radicum Syn Brassicae) and Thementioning
confidence: 99%
See 1 more Smart Citation
“…Gravid females of the cabbage root fly arrive at a hostplant odour source by a series of short upwind flights, landing and reorientating into the wind between flights (Hopkins et al, 1999). The adult female oviposits in the soil close to the stem of Brassica plants (Nottingham and Coaker, 1985;De Jong and Städler, 1999), while damage to the plants is caused by hatched larvae feeding on the roots.…”
Section: The Cabbage Root Fly (Delia Radicum Syn Brassicae) and Thementioning
confidence: 99%
“…Only mated gravid females respond to them (Hawkes and Coaker, 1979;Nottingham and Coaker, 1985;Renwick et al, 1992;Roessingh et al, 1992;Simmonds et al, 1994;De Jong and Städler, 1999;Hurter et al, 1999). In a study examining the role of glucosinolates towards oviposition behaviour of the cabbage root fly using egg counts and electrophysiological recordings from tarsal chemoreceptors, Roessingh et al (1992) showed that the D sensilla on segments 3 and 4 of the tarsus of cabbage root fly females contain a sensitive receptor cell for glucosinolates.…”
Section: Cabbage and Turnip Root Flies (Delia Radicum And D Floralis)mentioning
confidence: 99%
“…Both modes of chemical perception are known to be important for oviposition in the cabbage root fly (e.g. Roessingh et al 1997;De Jong & Städler 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Such synergistic effects of volatile host-plant compounds have been observed in different insects (refs in Städler 2002). An example reported by de Jong and Städler (1999) is the effect of Brassica volatiles, probably including ITC, on the oviposition behaviour of Delia radicum in contact with the host plant. The authors found no difference in the number of landings of flies but more mature females descended from these leaves when odour was present.…”
Section: Insect Reactions To Wax and Gs Interactionsmentioning
confidence: 99%